2017
DOI: 10.1002/cncr.30594
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into melanoma brain metastases

Abstract: Substantial proportions of patients with metastatic melanoma develop brain metastases during the course of their disease, often resulting in significant morbidity and death. Despite recent advances with BRAF/MEK and immune-checkpoint inhibitors in the treatment of patients who have melanoma with extracerebral metastases, patients who have melanoma brain metastases still have poor overall survival, highlighting the need for further therapy options. A deeper understanding of the molecular pathways involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 117 publications
0
36
0
Order By: Relevance
“…Our understanding of the brain‐homing process has been rather limited because research focused on brain dissemination has been restricted by the paucity of available preclinical models and human specimens annotated for development of cerebral lesions. The emergence of newer studies of key molecules involved in brain metastasis has added some new insights to our current understanding of the pathogenesis of disease while providing new opportunities for developing brain metastasis–specific therapies …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of the brain‐homing process has been rather limited because research focused on brain dissemination has been restricted by the paucity of available preclinical models and human specimens annotated for development of cerebral lesions. The emergence of newer studies of key molecules involved in brain metastasis has added some new insights to our current understanding of the pathogenesis of disease while providing new opportunities for developing brain metastasis–specific therapies …”
Section: Introductionmentioning
confidence: 99%
“…The emergence of newer studies of key molecules involved in brain metastasis has added some new insights to our current understanding of the pathogenesis of disease while providing new opportunities for developing brain metastasis-specific therapies. [8][9][10][11][12][13][14][15][16] Using an integrated clinical and bench-based approach, we previously showed that melanomas that tend to spread, survive, and proliferate in the central nervous system (brain-tropic) display distinct molecular features. 13 Our study identified PLEKHA5, a gene involved in normal brain development, as a likely mediator of melanoma brain dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…It is well accepted that advanced melanoma patients with brain metastases generally have a dismal prognosis, with limited benefit to therapeutic interventions other than surgery or radiotherapy. This can be at least partially explained by a very unique microenvironment, distinguished by the presence of a functional blood–brain barrier that limits the passage of molecular and cellular elements . Similarly, nonvisceral metastases are associated with a better survival relative to visceral metastases, and metastases in certain organs such as adrenal glands and lungs can be more responsive to treatment than others .…”
Section: Disrupting Cancer Immune Escapementioning
confidence: 99%
“…A majority of these patients show multiple brain lesions and/or meningeal involvement, and these factors are associated with particularly poor prognosis [2,5]. While current treatment options for patients with a limited number of brain parenchymal lesions include surgical resection and stereotactic radiosurgery, the treatment options for patients with multifocal disease and meningeal involvement are mainly palliative and include whole-brain radiotherapy and chemotherapy [1,7,8]. Recently, the introduction of molecularly targeted therapies and immunotherapy has given hope to patients with advanced melanoma [9,10], and several trials are evaluating the effect of BRAF inhibitors and immune checkpoint inhibitors in patients with brain metastases [1,11].…”
mentioning
confidence: 99%